Comparison of a once Daily with a twice Daily Subcutaneous Low Molecular Weight Heparin Regimen in the Treatment of Deep Vein Thrombosis - Charbonnier, Bernard A.; Fiessinger, Jean-Noël; Banga, J. D.; Wenzel, Ernst; d’Azemar, Pascal; Sagnard, Luc; FRAXODI group (Thrombosis and Haemostasis, 1998)
Background: Clinical trials have been performed to compare with standard heparin a once or a twice daily regimen of low-molecular-weight heparin but no direct comparison has been done between these two low-molecular-weight heparin regimens in terms of efficacy and safety with a long-term clinical evaluation.Methods: Patients with proximal deep vein thrombosis, confirmed by venography were randomly assigned to either nadroparin (10,250 AXa IU/ml) twice daily or nadroparin (20,500 AXa IU/ml) once daily for at least 5 days. Regimens were adjusted to bodyweight. Oral anticoagulants were started on day 1 or 2 and continued for 3 months. Patients were followed up for 3 months. The composite outcome of venous thromboembolism and death possibly related to pulmonary embolism was the primary measure of efficacy. Major bleeding was the principal measure of safety. The study was designed to show equivalence between the two regimens.Results: Recurrent thromboembolic events or death possibly related to pulmonary embolism were reported in 13 patients in the once daily group (4.1%) and in 24 patients of the twice daily group (7.2%): (absolute difference 3.1% in favor of the once daily regimen; 95% confidence interval -6.6%, +0.5%). Major bleeding episodes during nadroparin treatment occurred in 4 (1.3%) and 4 patients (1.2%) in the once and twice daily groups, respectively.Conclusions: A nadroparin regimen of one injection per day is at least as effective and safe as the same total daily dose divided over two injections for the treatment of acute deep vein thrombosis.